An intradermal inoculation model of scrub typhus in Swiss CD-1 mice demonstrates more rapid dissemination of virulent strains of Orientia tsutsugamushi - Sunyakumthorn, P; Paris, D; Chan, T; Jones, M; Luce-Fedrow, A; Chattopadhyay, S; Jiang, J; Anantatat, T; Turner, G; Day, N; Richards, A (Public Library of Science, 2013)
Scrub typhus is an important endemic disease of the Asia-Pacific region caused by Orientia tsutsugamushi. To develop an effective vaccine to prevent scrub typhus infection, a better understanding of the initial host-pathogen interaction is needed. The objective of this study was to investigate early bacterial dissemination in a CD-1 Swiss outbred mouse model after intradermal injection of O. tsutsugamushi. Three human pathogenic strains of O. tsutsugamushi (Karp, Gilliam, and Woods) were chosen to investigate the early infection characteristics associated with bacterial virulence. Tissue biopsies of the intradermal injection site and draining lymph nodes were examined using histology and immunohistochemistry to characterize bacterial dissemination, and correlated with quantitative real-time PCR for O. tsutsugamushi in blood and tissue from major organs. Soluble adhesion molecules were measured to examine cellular activation in response to infection. No eschar formation was seen at the inoculation site and no clinical disease developed within the 7 day period of observation. However, O. tsutsugamushi was localized at the injection site and in the draining lymph nodes by day 7 post inoculation. Evidence of leukocyte and endothelial activation was present by day 7 with significantly raised levels of sL-selectin, sICAM-1 and sVCAM-1. Infection with the Karp strain was associated with earlier and higher bacterial loads and more extensive dissemination in various tissues than the less pathogenic Gilliam and Woods strains. The bacterial loads of O. tsutsugamushi were highest in the lungs and spleens of mice inoculated with Karp and Gilliam, but not Woods strains. Strains of higher virulence resulted in more rapid systemic infection and dissemination in this model. The CD-1 mouse intradermal inoculation model demonstrates features relevant to early scrub typhus infection in humans, including the development of regional lymphadenopathy, leukocyte activation and distant organ dissemination after low-dose intradermal injection with O. tsutsugamushi.